ZnO-embedded BiOI hybrid nanoflakes: Synthesis, characterization, and improved photocatalytic properties. (15th May 2017) - Tong, Yanhua; Zheng, Chu; Lang, Wenjing; Wu, Fan; Wu, Tao; Luo, Wenqin; Chen, Haifeng
Abstract: BiOI-based p–n heterostructures with enhanced visible-light photocatalytic activity have been investigated in detail. However, photocatalytic activity of most of heterostructures usually drops step by step with increasing irradiation time. The main reason for this deactivation is the instability of the loaded heterostructures. In this study, ZnO-embedded BiOI hybrid nanoflakes were fabricated using Zn5 (CO3 )2 (OH)6 ultrathin nanosheets for BiOI deposition followed by calcination. This embedded hybridized nanostructure showed strong coupling between ZnO and BiOI, different from those of ZnO-loaded BiOI heterostructures. The visible-light photodegradation experiments demonstrate that the ZnO-embedded BiOI hybrid nanoflakes not only exhibited remarkably enhanced and sustainable photocatalytic activity, but also showed good recyclability, comparing with the pristine ZnO, BiOI and ZnO/BiOI heterostructures. Integrated measurements of electrochemistry and photoelectrochemistry, photoluminescence and reactive species during the photodegradation process, substantial enhancement of photocatalytic activity for ZnO-embedded BiOI hybrid nanoflakes is probably attributed to the raised potential of valence-band edge, good conductivity, and quenching of deep-level defects. This study provides an embeddedly hybridized route to enhance photocatalytic activity and simultaneously improve their sustainability and recyclability. Graphical abstract: ZnO-embedded BiOI hybrid nanoflakes with enhanced and sustainable visible-light photocatalytic activity have been fabricated using Zn5 (CO3 )2 (OH)6 ultrathin nanosheets as template for BiOI deposition followed by calcination. Highlights: ZnO-embedded BiOI hybrid nanoflakes showed intimate coupling between ZnO and BiOI. This embedded hybrid nanostructure exhibited remarkably enhanced and sustainable photocatalytic activity. The enhanced catalytic activity of the embedded hybrid nanoflakes was discussed in details.